Geodynamic evolution of lithospheric removal of the North China Craton: Constraints from late Mesozoic volcanic rocks in the Bohai Bay Basin, East China. (15th September 2022) - Fu, Mao; Shan, Xuanlong; Zhang, Xintao; Yi, Jian; Xu, Chunqiang; Wang, Chenjie; Yue, Junpei
Graphical abstract: Highlights: Late Mesozoic volanic rocks in North China record history of lithospheric removal. Local slab rollback caused delamination of thickened lower crust in Late Jurassic. Large-scale rollback was related to eastward delamination in Early Cretaceous. Lithospheric removal was induced by two-stage slab rollback processes. Large-scale lithospheric removal ended after ca. 115 Ma. Abstract: The subduction history of Paleo-Pacific Plate (PPP) related to lithospheric removal in the North China Craton (NCC) still poorly constrained. To address this issue, we report a detailed investigation of LA-ICP–MS zircon U–Pb chronology, geochemistry, and Sr-Nd isotope compositions of a set of late Mesozoic volcanic rocks collected from boreholes in the Bohai Bay Basin. Late Jurassic (150.6 Ma) adakitic rocks are trachyandesites with high MgO (1.41–5.78 wt%), Mg # (46–64), Cr (25.1–110 ppm) and Ni (12.4–34.0 ppm) contents similar to those of high-Mg adakitic rocks. These samples were probably the result of partial melting of a delaminated region of thickened lower continental crust. Early Cretaceous samples are basalt and trachyandesite. Trachyandesites (ca. 115 Ma) exhibit low εNd(t) values (-15.9 to −12.9) and older TDM2 ages (2.19–1.96 Ga), indicating that they originated in the ancient lower crust. Hornblende may have been the main residual phase in the source, suggesting that these samples were likely formed by partial melting of the lower crust at depths of 30–40 km. The coeval basalts are OIB-like series with depleted Sr-Nd isotopes, depleted Pb and no depleted Nb, implying that they were derived from a depleted mantle source metasomatized by recycled oceanic crust. Combined with those of previous studies, our findings show that subducted PPP beneath the NCC experienced local slab rollback and fast slab rollback during late Mesozoic, resulting in lithospheric removal and destruction of the NCC. Finally, the magmatic activity that marked the large-scale lithosphere removal ended after ca. 115 Ma.